Waste management of the coastal areas in the ASEAN region roles of government, banking institutions, donor agencies, private sector and communities. (Manila, Philippines ICLARM, 1992)
ICLARM Conf. Proc. (33)
Keywords: Environment management; Coastal zone management; Pollution control; Marine pollution; Waste disposal